Kininogen enhances seizure susceptibility in mice possibly through bradykinin-induced modulation of calcium transients in glutamatergic and GABAergic neurons - Ghosh, Arijit; Huang, Jiwen; Wang, Qian; Gong, Yanling; Jain, Srishti; Thakur, Abhimanyu; De, Amiyangshu; Gong, Meixi; Kiyohara, Yoshie; Hu, Jingtai; Jin, Lingyan; Bandyopadhyay, Sharba; et al. (Frontiers in Pharmacology, 2025)
BackgroundPreviously we showed that elevated cerebrospinal fluid (CSF) levels of kininogen during the acute phase of encephalitis are associated with symptomatic epilepsy. However, the functional role of kininogen in epileptogenesis remains unexplored.ObjectiveThis study investigated the brain expression of kininogen and its influence on seizure susceptibility. Additionally, we examined the effects of bradykinin, a nonapeptide derived from kininogen, as a potential downstream mediator of kininogen's effect on seizure susceptibility and the underlying circuitry mechanisms.MethodsWe analyzed brain mRNA expression of kininogen using publicly available single-cell RNA-sequencing (scRNA-seq) datasets and assessed protein expression through immunofluorescence in various brain regions. Immunoblot was conducted following pilocarpine-induced status epilepticus (Pilo-SE) to understand post-seizure kininogen dynamics. Next, to understand its functional role, kininogen was overexpressed in the hippocampal CA1 area via its AAV-mediated gene delivery, and bradykinin was administered through the fourth ventricle in mice. The effects on seizure susceptibility were evaluated using a pentylenetetrazole-induced seizure susceptibility test. Furthermore, two-photon in vivo calcium imaging of cortical layer 2/3 glutamatergic neurons and GABAergic parvalbumin-positive neurons was performed to explore the potential circuitry mechanisms.ResultsWhile scRNA-seq analyses found kininogen gene expressions in various cell types across the brain, immunofluorescence revealed its preferential localization in neurons but not in glia. Pilo-SE decreased intact kininogen levels in the hippocampus and increased cleaved to intact kininogen (cHK / iHK) ratio. Overexpression of kininogen and exogenous bradykinin administration significantly increased pentylenetetrazole-induced seizure susceptibility in mice. Mechanistically, bradykinin was found to enhance calcium activities in cortical glutamatergic excitatory neurons in Thy1-GCaMP mice when they were treated with a subthreshold dose of pentylenetetrazole. In contrast, calcium activities in GABAergic parvalbumin-positive inhibitory neurons were reduced by bradykinin in PVCre-GCaMP mice, suggesting potential circuitry mechanisms by which kininogen may render increased seizure susceptibility.ConclusionOur findings reveal a novel pathological role of kininogen in seizure occurrence, explaining why kininogen might be elevated in the CSF of epilepsy-susceptible patients and suggest its potential mechanisms where it might regulate the activities of glutamatergic and GABAergic neurons through the downstream release of bradykinin. Altogether, we propose kininogen as a potential target for developing therapeutics for epilepsy intervention.